Disturbances of Vaginal Microbiome Composition in Human Papillomavirus Infection and Cervical Carcinogenesis: A Qualitative Systematic Review - Wu, Ming; Li, Huanrong; Yu, Hongfei; Yan, Ye; Wang, Chen; Teng, Fei; Fan, Aiping; Xue, Fengxia (Frontiers in Oncology, 2022)
Background Emerging evidence has demonstrated a close association between perturbations in vaginal microbiota composition in women and human papillomavirus (HPV) infection, cervical lesions, and cervical cancer (Ca); however, these findings are highly heterogeneous and inconclusive. Aim To perform a comprehensive systematic review of the global disturbance in the vaginal microbiota, specifically in women with HPV-associated cervical diseases, and to further conduct within- and across-disease comparisons. Method Twenty-two records were identified in a systematic literature search of PubMed, Web of Science, and Embase up to February 28, 2022. We extracted microbial changes at the community (alpha and beta diversity) and taxonomic (relative abundance) levels. Within- and across-disease findings on the relative abundance of taxonomic assignments were qualitatively synthesized. Results Generally, significantly higher alpha diversity was observed for HPV infection, cervical lesions, and/or cancer patients than in controls, and significant differences within beta diversity were observed for the overall microbial composition across samples. In within-disease comparisons, the genera Gardnerella, Megasphaera, Prevotella, Peptostreptococcus, and Streptococcus showed the greatest abundances with HPV infection; Sneathia and Atopobium showed inconsistent abundance with HPV infection, and Staphylococcus was observed in Ca. Across diseases, we find increased levels of Streptococcus and varying levels of Gardnerella were shared across HPV infections, high-grade squamous intraepithelial lesions, and Ca, whereas Lactobacillus iners varied depending on the HPV-related disease subtype. Conclusions This systematic review reports that vaginal microbiome disturbances are correlated to the depletion of Lactobacillus, enrichment of anaerobes, and increased abundance of aerobic bacteria in HPV infection and related cervical diseases. Moreover, L. iners may exert either protective or pathogenic effects on different HPV-related diseases.